Structural changes of silver carp myosin glycated with Konjac oligo-glucomannan: Effects of deacetylation. (June 2019) - Liu, Jianhua; Fang, Chunhua; Xu, Xia; Su, Qi; Zhao, Peicheng; Ding, Yuting
Abstract: The glycation of silver carp ( Hypophthalmichthys molitrix ) myosin (Ms) with konjac oligo-glucomannan (KOG) of different deacetylation degrees (DDs) was investigated, in an attempt to detect the structural changes of myosin. As DD increased in KOG, glycation changed the composition of amino acids in myosin, and the surface hydrophobicity ( H 0 ) of glycoconjugates decreased. Fourier transform infrared spectroscopy (FT-IR) and circular dichroism (CD) spectroscopy exhibited the significant changes of the primary and secondary structure. The increase of denaturation temperature from DSC spectra and the changes of intrinsic fluorescence emission spectra revealed that the changes in the folded state of myosin occurred, indicating that the thermal stability or the tertiary/quaternary structural stability of myosin can be improved by the glycation with KOG of different DDs. The results from scanning electron microscope (SEM) and atomic force microscope (AFM) demonstrated that when deacetylated KOGs (DKOGs) were used as sugar donor, the glycoconjugates were larger and the surface structure is more dispersed than myosin alone. It can be suggested that myosin holds a more flexible conformation after glycation with DKOGs, which is more suitable for its various excellent functional properties. Graphical abstract: Image 107447 Highlights: The denaturation temperature of Ms was increased after glycation with DKOGs. The surface hydrophobicity of Ms was decreased after glycation with DKOGs. DKOG improved the flexibility in conformation and enhanced the steric hindrance of Ms.